Findings of intraformational striated pavements in the late carboniferous glacial deposits of the Andean Precordillera, Argentina - Pablo J. Alonso Muruaga; Carlos O. Limarino; Luis A. Spalletti; Ferrán Colombo Piñol; Pablo Juárez (Latin American Journal of Sedimentology and Basin Analysis, 2021)
One of the most important glacial events in the history of the Earth took place during the Late Paleozoic when large areas of the Gondwana Supercontinent were covered by ice-masses (Crowell, 1978; Hambrey and Harland, 1981; Isbell et al., 2003a,b; Rocha Campos et al., 2008; Fielding et al., 2008; López Gamundí, 2010). Though this glacial event was initially considered a large and unique episode spanning a great part of the Carboniferous and Permian in Gondwana, new geological evidence suggests that the glacial period was not continuous, but rather punctuated by several interglacial events. In this way, López Gamundí (1997) and later Isbell et al. (2003b) divided the Late Paleozoic Ice Age (LPIA) into four major glacial intervals corresponding to the Early Carboniferous (LPIA 1), Late Carboniferous- Early Permian (LPIA 2), Early Permian (LPIA 3) and Late Permian (LPIA 4). This division adequately describes the record of the glacial deposits in Gondwana and allows for the proposal of a general stratigraphy for the glacial deposits demonstrating the existence of low-frequency climatic changes. In this paper we describe two subglacial basal contact surfaces found in the lower part of the Guandacol Formation (Frenguelli, 1944; Cuerda, 1965) in the Central Precordillera (northwestern Argentina). The Guandacol Formation is well known for containing glacial deposits, including diamictites and resedimented diamictites at the lower third of the unit (Limarino et al., 2006; Marenssi et al., 2002; Marenssi et al., 2005). According to paleontological (palynological) information, and some radiometric dating, the age of the glacial deposits is Late Visean- Early Bashkirian and therefore fits into the LPIA 2 interval of Isbell et al. (2003b).